A Novel Intergenic Gene Between SLC8A1 and PKDCC-ALK Fusion Responds to ALK TKI WX-0593 in Lung Adenocarcinoma: A Case Report - Du, Jia; Wang, Baoming; Li, Mengxia; Wang, Chunyang; Ma, Tonghui; Shan, Jinlu (Frontiers in Oncology, 2022)
Background Expanding the druggable novel anaplastic lymphoma kinase (ALK) fusions list is crucial to the precise treatment of patients with cancer with positive ALK fusions. The intergenic-ALK fusions accounted for a substantial proportion of ALK fusions. However, they were typically considered of limited clinical significance due to the obscure functional partners. In this case report, a patient carrying intergenic-ALK fusion presents an excellent outcome after taking the new second-generation tyrosine kinase inhibitor (TKI) candidate, WX-0593. Case Presentation A 47-year-old Chinese female patient diagnosed with IVB lung adenocarcinoma was admitted to the hospital with large dimension lesions in the left lobe of the lung. After 1 week of first line chemotherapy, no response was found. A novel ALK rearrangement generated by a fusion of the intergenic region between SLC8A1 and PKDCC to the intron 19 of ALK was presented after next-generation sequencing and was further confirmed by Sanger’s sequencing. High expression of ALK was revealed by immunohistochemistry. The patient was directed to engage in phase III clinical trial (NCT04632758) and received an orally active second-generation ALK inhibitor WX-0593. Over the course of 17 months, the partial response was obtained without significant side effects. Conclusion In summary, a patient with non–small cell lung cancer harboring a novel intergenic-ALK fusion, whose intergenic breakpoint was located between SLC8A1 and PKDCC, benefited from a potent ALK TKI candidate WX-0593. This finding extended the scope of targetable ALK fusions. More importantly, it highlighted the advantages of next-generation sequencing in identifying rare but functional ALK fusions, which eventually benefit patients.